Integration Of Population Identification Number (NIK) As Taxpayer Identification Number (NPWP) For Optimizing Tax Compliance: Case Study At Pondok Aren Pratama Tax Service Office - Aribowo, Irwan; Kusuma, I Gede Komang Chahya Bayu Anta; Suryono, Agus; Muluk, M.R. Khairul; Wijaya, Andy Fefta (Educoretax, 2024)
This research focuses on analyzing the effect of integrating the Population Identification Number (NIK) as a Taxpayer Identification Number (NPWP) on optimizing tax compliance for Individual Taxpayers (WPOP) at the Pondok Aren Pratama Tax Service Office (KPP Pratama Pondok Aren). The main motivation of this research is to evaluate the extent to which the integration of NIK as a NPWP can increase tax compliance and tax administration efficiency. Using a descriptive qualitative approach, this research collected primary data through interviews with Taxpayers registered at Pondok Aren Pratama Tax Service Office. The research results show that the majority of Taxpayers do not understand the process and importance of integrating NIK as NPWP. However, effective outreach and increased awareness can encourage better tax compliance. This research provides an important contribution to understanding regarding the implementation of tax policies and strategies to increase tax compliance in Indonesia.